Organizações sindicais, Estado e sociedade civil no Brasil - Segatto, José Antonio [UNESP] (My University, 2010)
During a long historical process of over a century, the trade union movement gathered a significant amount of achievements. The limits and the extent of these achievements cannot be dissociated form the complex relations between State and civil society in Brazil.

No decorrer de um largo processo histórico, de mais de um século, o movimento sindical acumulou um importante patrimônio de conquistas. Os limites e a extensão dessas aquisições não podem ser dissociados das complexas relações entre o Estado e a sociedade civil no Brasil.
Trade union organizations, state and civil society in Brazil
Keywords: Trade unions; State, Civil society; Citizenship; Corporatism; Sindicatos; Estado; Sociedade civil; Cidadania; Corporativismo